A Compact Antenna with WiMAX and WLAN bands notched for UWB applications - V.Prashanth, K; Umamaheswari, Bonthu; Akhil, G; Vamsi krishna, G; Venkata Sai chandu, M (International Journal of Engineering and Technology, 2018)
A Compact antenna with WiMAX and WLAN bands notched for ultra wide band (UWB) applications is proposed. The proposed antenna is designed for the planar ultra wide band (UWB) antenna and ultra wide band (UWB) antenna having two band rejections. The proposed antenna overall size is 30mm x 40mm x 1.6mm. The antenna consists of a rectangular patch on the top of FR4 substrate with 50ohm feed with defected ground structure. This patch consists of one round cut at each corner having radius 1.575mm. The simulated band width with return loss (RL) >=10db is 3.1 to 11.2 GHz with VSWR
Keywords: Compact; Dual Notch; Rectangular patch antenna; Ultra-wide band (UWB); VSWR.